The Effect of Work Stress on the Employee Performance at the Regional Office of DJP Sulselbartra - Fadhilah Atikah Sari; Riny Jefri; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This study's purpose is to obtain empirical evidence if there is an effect of work stress on the employee performance and the most influential factor on employee performance. This research was conducted at the Regional Office of DJP Sulselbartra. The independent variable in this study is work stress, while employee performance is the dependent variable. The research method used is direct distributing questionnaires to employees at the Regional Office of DJP Sulselbartra. The number of respondents collected in this study, namely 65 respondents. The data analysis test used is the simple linear regression method. Based on the results of the tests that have been carried out, it shows that the work stress variable has a significant effect on the employee performance variable at the Regional Office of DJP Sulselbartra.